Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
{2x-y = -5 => -y=-5-2x /*(-1) y=2x+5
{-x+-y =10
Substitute y in the second equation:
-x-y=10
-x-(2x+5)=10
-x-2x-5=10
-3x-5=10 /+5
-3x=15 /:(-3)
x=-5
y=2x+5=2*(-5)+5=-10+5=-5
y=-5
Solution: (-5; -5)
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.